Characterization of particulate organic nitrates in the Yangtze River Delta, East China, using the time-of-flight aerosol chemical speciation monitor. (1st March 2022) - Ge, Dafeng; Nie, Wei; Sun, Peng; Liu, Yuliang; Wang, Tianyi; Wang, Jinbo; Wang, Jiaping; Wang, Lei; Zhu, Caijun; Wang, Ruoxian; Liu, Tengyu; Chi, Xuguang; et al.
Abstract: Particulate organic nitrates (pON) are important species in the atmosphere that influence reactive nitrogen cycling and ozone (O3 ) formation. Previous studies on pON focused on forest regions involving anthropogenic NOx emissions. Therefore, the investigation and quantitation of pON in polluted urban regions remain limited. Here, we conducted sampling campaigns in four seasons using an Aerodyne time-of-flight aerosol chemical speciation monitor in the SORPES station in Nanjing, East China. pON were calculated using a constrained-PMF method, which was validated using high-resolution aerosol mass spectrometer-based estimates. The results reveal that pON contribute significantly to the aerosol nitrate in the polluted Yangtze River Delta, and the fractions of pON to total nitrate are >21% in the summer, spring, and autumn, and >13% in the winter. The pON contribution to the total nitrate decreases as the fine particulate matter (PM2.5 ) loading increases but remaines significant at the peak of pollution. This indicates that the pON formation is controlled by the gas-phase chemistry, which is pronounced during low PM2.5 pollution. pON are also associated with organic matter (OM), and its contribution to the OM is independent of the PM2.5 loading. The contributions to OM are 36.2%, 25.6%, 24.1%, and 13.9% during the winter, autumn, spring, and summer, respectively. Our study demonstrates that pON are potentially important components of atmospheric PM2.5 in urban areas. Highlights: ● Particulate organic nitrates (pON), estimated by constrained-PMF with the time-of-flight aerosol chemical speciation monitor, contributed significantly to aerosol nitrate and organic matter in the Yangtze River Delta. ● The pON contribution to the total nitrate revealed strong seasonal and diurnal variation. ● The pON contribution to the total nitrate decreased as thePM2.5 loading increased, while its contribution to organic matter was independent of the PM2.5 loading.